2005
DOI: 10.1097/01.jom.0000147211.63924.87
|View full text |Cite
|
Sign up to set email alerts
|

The Community Initiative on Depression: Report from a Multiphase Work Site Depression Intervention

Abstract: Depression is a prevalent illness with risk for many deleterious outcomes if under-recognized or undertreated. Depression is a leading cause of work-related disability worldwide. Most people with depression are employed (an estimated 68%). Recognizing and initiating depression care in the workplace will facilitate depression treatment in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…In a study of 6,399 employees from 13 workplaces, Charbonneau et al (2005) found that although 62% knew how to access company resources for depression care, only 29% indicated they would feel comfortable discussing the issue with their supervisor. Their reluctance is not without foundation given that in the United States mental disorders are the second most common basis for charges of discrimination and workplace harassment (Stuart, 2006).…”
Section: Current Issues In Managing Depression In the Workplacementioning
confidence: 97%
“…In a study of 6,399 employees from 13 workplaces, Charbonneau et al (2005) found that although 62% knew how to access company resources for depression care, only 29% indicated they would feel comfortable discussing the issue with their supervisor. Their reluctance is not without foundation given that in the United States mental disorders are the second most common basis for charges of discrimination and workplace harassment (Stuart, 2006).…”
Section: Current Issues In Managing Depression In the Workplacementioning
confidence: 97%
“…These studies did not include a diagnosis of depression with a validated screening instrument (Bender and Farvolden 2008;Billings et al 2008;Caruso and Myette 2008;Charbonneau et al 2005;Colombi 2005;Davies 2008;Dunnagan et al 2001;Hauck and Chard 2009;Kitchener and Jorm 2004;Langlieb and Kahn 2005;(Millear et al 2008;Nakayama and Amagasa 2004;Renaud et al 2008;Zivin et al 2009). Amongst the 27 unselected studies, one used a control group; however, the study presented a programme in progress with no published results yet (Martin et al 2009b).…”
Section: Study Characteristics Of Unselected Studymentioning
confidence: 97%
“…According to workplace-based surveys, most working individuals say that they would be comfortable discussing depression with their physician, but only a minority would feel comfortable discussing depression with their supervisor [31]. Unfortunately, even professionals such as working physicians being observed by psychiatrists can be subject to discrimination by overseeing bodies due to invasive policies.…”
Section: Stigma and Discriminationmentioning
confidence: 95%
“…Additionally, differential outcomes, such as employment, have been observed in depressed minority patients as compared with nonminority patients. This appears to be largely influenced by the nature of treatment received and acceptance of treatment, suggesting the influence of cultural and socioeconomic factors [31,32].…”
Section: Stigma and Discriminationmentioning
confidence: 95%
See 1 more Smart Citation